Computer-Navigated versus Conventional Total Knee Arthroplasty: A Meta-Analysis of Functional Outcomes from Level I and II Randomized Controlled Trials - Chin, Brian Zhaojie; Seck, Victor Mun Hin; Syn, Nicholas Li-Xun; Wee, Ian Jun Yan; Tan, Sharon Si Heng; O’Neill, Gavin Kane (The Journal of Knee Surgery, 2019)
The main purpose of this article is to provide an up-to-date systematic review and meta-analysis comparing functional outcomes of total knee arthroplasty using either computer navigation (NAV-TKA) or conventional methods (CON-TKA) from the latest assemblage of evidence. This study was conducted according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses and Meta-Analysis of Observational Studies in Epidemiology guidelines. All Level I and II randomized controlled trials (RCTs) in PubMed, EMBASE, and Cochrane that compared functional outcomes after NAV- and CON-TKA were included in the review. Selected end points for random effects, pairwise meta-analysis included Knee Society Knee Score (KSKS), KS Function Score (KSFS), KS Total Score (KSTS), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and range of motion at three arbitrary follow-up times. A total of 24 prospective RCTs comprising 3,778 knees were included from the initial search. At long-term follow-up (>5 years), NAV-TKA exhibited significantly better raw KSKS (p = 0.001) (low-quality evidence), contrary to CON-TKA, which reflected significantly better raw KSTS (p = 0.004) (high-quality evidence). While change scores (KSKS, WOMAC) from preoperative values favor CON-TKA at short-term (<6 months) and medium-term follow-up (6–60 months), long-term follow-up change scores in KSKS suggest the superiority of NAV-TKA over CON-TKA (p = 0.02) (very low-quality evidence). Overall, sizeable dispersion of nonstatistically significant functional outcomes in the medium term was observed to eventually converge in the long term, with less differences in functional outcome scores between the two treatment methods in short- and long-term follow-up. While raw functional outcome scores reflect no differences between NAV and CON-TKA, long-term follow-up change scores in KSKS suggest superiority of NAV-TKA over its conventional counterpart. Prospective studies with larger power are required to support the pattern of diminishing differences in functional outcome scores from medium- to long-term follow-up between the two modalities.
Keywords: navigation; conventional; total knee arthroplasty; computer-navigated; clinical outcomes; functional outcome